1980
DOI: 10.3382/ps.0590772
|View full text |Cite
|
Sign up to set email alerts
|

Disease, Nutrition—Interaction

Abstract: Practical implications of interactions between disease and vitamins in poultry were sought in the readily available literature. The evidence, almost exclusively in chickens, is in accord with that reported in other animals and man, namely 1) dietary vitamin deficiencies can impair body defense mechanisms against disease and 2) occurrence of disease can increase vitamin requirements.Information on viral infections is inadequate and conflicting. Slight indications exist for positive interactions with ascorbic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The standard dietary supplementation with proteins, carbohydrates, lipids, minerals, and vitamins supports normal growth of birds. Similarly, the standard supplementation with certain minerals and vitamins helps to increase the birds’ immune resistance against pathogenic diseases [ 17 , 18 , 19 , 20 ]. The dietary requirement for vitamin E in poultry feed is highly variable and depends on the concentration and type of fat in the diet, the concentration of selenium, and the presence of pro-oxidants and antioxidants [ 21 ].…”
Section: Vitamin E In Poultry Nutritionmentioning
confidence: 99%
“…The standard dietary supplementation with proteins, carbohydrates, lipids, minerals, and vitamins supports normal growth of birds. Similarly, the standard supplementation with certain minerals and vitamins helps to increase the birds’ immune resistance against pathogenic diseases [ 17 , 18 , 19 , 20 ]. The dietary requirement for vitamin E in poultry feed is highly variable and depends on the concentration and type of fat in the diet, the concentration of selenium, and the presence of pro-oxidants and antioxidants [ 21 ].…”
Section: Vitamin E In Poultry Nutritionmentioning
confidence: 99%
“…Several researchers and reviewers (Axelrod and Traketellis, 1964;Beisel, 1582;Blalock et al, 1985;CunninghamRundles, 1982;Debes and Kirksey, 1979;Scott et al, 1976;Wilgus, 1977) have reported that deficiency of pyriodoxine suppresses the immune response in a number of animals. The requirement is dependent, in part, on the amount of dietary protein (Scott et al, 1976), Hardy et al (1979) found that increased pyriioxine in a high-protein diet rendered chinook salmon fingerlings more resistant to Vibrio anguillarum, but additional pyridoxine have been demonstrated to be dramatically affected by reduced pyridoxine, as evidenced by depressed mixed lymphocyte reactivity, prolonged allograft survival, and reduced skin hypersensitivity (Axelrod and Traketellis, 1964).…”
mentioning
confidence: 99%
“…Many vitamins h a v significant roles in the functioning of immune systems in man and other animals. Several researchers and reviewers (Axelrod and Traketellis, 1964;Beisel, 1582;Blalock et al, 1985;Cunningham-Rundles, 1982;Debes and Kirksey, 1979;Scott et al, 1976;Wilgus, 1977) have reported that deficiency of pyriodoxine suppresses the immune response in a number of animals. The requirement is dependent, in part, on the amount of dietary protein (Scott et al, 1976), Hardy et al (1979) found that increased pyriioxine in a high-protein diet rendered chinook salmon fingerlings more resistant to Vibrio anguillarum, but additional pyridoxine have been demonstrated to be dramatically affected by reduced pyridoxine, as evidenced by depressed mixed lymphocyte reactivity, prolonged allograft survival, and reduced skin hypersensitivity (Axelrod and Traketellis, 1964).…”
mentioning
confidence: 99%